2020
DOI: 10.1021/acs.jpclett.0c01285
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Atomically Irreversible Cation Migration in Sodium Layered Oxide Cathodes

Abstract: Transition metal (TM)-based layered oxides NaTMO 2 (TM = Fe, Ni, Co, Mn, etc.) have been intensively pursued as high-capacity cathode materials for Na-ion batteries. Nevertheless, they still suffer from fast capacity loss and voltage decay, as a result of the layered structure instability upon extended electrochemical cycling. The mechanism underlying such instability remains poorly understood. Here we unravel the TM migrations and structural evolution of a quaternary NaNi 0.3 Co 0.12 Mn 0.18 Fe 0.4 O 2 compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…To gain a greater understanding of which transition metal ions preferentially migrate into the Na layer during electrochemical cycling, Chen et al used atomic resolution scanning tunnel electron microscopy in combination with energy dispersive X-ray spectrometry (STEM-EDS) elemental mapping to study the quaternary NaNi 0.3 Co 0.12 Mn 0.12 Fe 0.4 O 2 composition. 79 They found that Fe migrates into both tetrahedral and octahedral sites within the Na layer, as depicted in Fig. 11.…”
Section: Transition Metal Migrationmentioning
confidence: 94%
See 1 more Smart Citation
“…To gain a greater understanding of which transition metal ions preferentially migrate into the Na layer during electrochemical cycling, Chen et al used atomic resolution scanning tunnel electron microscopy in combination with energy dispersive X-ray spectrometry (STEM-EDS) elemental mapping to study the quaternary NaNi 0.3 Co 0.12 Mn 0.12 Fe 0.4 O 2 composition. 79 They found that Fe migrates into both tetrahedral and octahedral sites within the Na layer, as depicted in Fig. 11.…”
Section: Transition Metal Migrationmentioning
confidence: 94%
“…72 The strong electrostatic interactions (attraction with the oxygen layers, leading to a decrease in the interlayer spacing, and repulsion with the approaching sodium ions) induced by the migrated transition metal ions is thought to have a detrimental impact on the reinsertion of sodium ions. 79 Using DFT simulations, Zhang et al went on to show that the energy penalty for migration of a transition metal ion is inuenced by its neighbouring transition metal ions. 80 More specically, they showed that the shortened Fe-O bond length with neighbouring Cu (due to the large electronegativity of Cu) can signicantly enhance the energy penalty, effectively preventing the Fe migration into the Na layer.…”
Section: Transition Metal Migrationmentioning
confidence: 99%
“…Here, we prefer to only consider the migration of nickel rather than manganese, since the migration of iron and nickel ions to the AM layers has been observed. [46][47][48][49][50] Meanwhile, our DFT calculation outcomes show that O2 structures with Ni migration are more stable than with Mn migration (Fig. S5 †).…”
Section: Adverse Effects Of Ca 2+ Ionsmentioning
confidence: 89%
“…Spherical NNCM compound aggregates in micron size were synthesized through coprecipitation plus solid-state calcination processes (Extended Data Fig. 1), as reported in our previous studies 21,22 . The XRD pattern for the pristine NNCM is indexed as typical O3-type R3(_)m phase, and this layered structure is well maintained after electrochemical cycling (Extended Data Fig.…”
Section: Main Textmentioning
confidence: 99%